To solve the equation \(3(6x - 1) + 4x = 4(3x - 1) - 5\), let's start by simplifying both sides step by step.
Step 1: Distribute on both sides.
On the left-hand side: \[ 3(6x - 1) = 18x - 3 \] So the left-hand side becomes: \[ 18x - 3 + 4x = 22x - 3 \]
On the right-hand side: \[ 4(3x - 1) = 12x - 4 \] So the right-hand side becomes: \[ 12x - 4 - 5 = 12x - 9 \]
Now the equation is: \[ 22x - 3 = 12x - 9 \]
Step 2: Combine like terms.
Subtract \(12x\) from both sides: \[ 22x - 12x - 3 = -9 \] This simplifies to: \[ 10x - 3 = -9 \]
Step 3: Isolate \(x\).
Add 3 to both sides: \[ 10x = -9 + 3 \] This simplifies to: \[ 10x = -6 \]
Now, divide both sides by 10: \[ x = -\frac{6}{10} = -\frac{3}{5} \]
So, the solution in simplest form is: \[ \boxed{-\frac{3}{5}} \]